Relación entre el ruido ambiental y la percepción acústica en pobladores de la avenida participación Iquitos 2022 - Echegaray Reátegui, Alejandro Wilson (2024)
This research explores changes in daily activities throughout history, from antiquity to the present, with the aim of analyzing the relationship between environmental noise and acoustic perception. The methodology included monitoring environmental noise in the field using a Class 1 measurement instrument, as well as conducting surveys with 357 residents of Avenida Participación to assess their sound perception. The results revealed an average of 79.09 dB for the first variable and 63.80 for the second, indicating a very high sound perception. The correlation between both variables was 64.6%, classified as moderate. In conclusion, it is observed that the noise level exceeds environmental quality standards, and acoustic perception among residents is significantly high.